2010
DOI: 10.1111/j.1600-9657.2010.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Crown and crown–root fractures: an evaluation of the treatment plans for management proposed by 154 specialists in restorative dentistry

Abstract: Traumatic tooth injuries involve function and aesthetics and cause damage that range from minimal enamel loss to complex fractures involving the pulp tissue and even loss of the tooth crown. Technical knowledge and clinical experience are essential to establish an accurate diagnosis and provide a rational treatment. The purpose of this study was to evaluate the knowledge of Restorative Dentistry specialists about the management of crown and crown-root fractures based on treatment plans proposed by these profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
0
20
1
3
Order By: Relevance
“…11,14 The findings of the present study revealed that, in general, the level of knowledge of the dentists interviewed was low, notwithstanding the existence of clinical protocols in the literature that indicate the most adequate treatment approaches for each type of injury. 8,15 There is a low incidence of dentoalveolar traumas in clinical practice and, as a result, there is little experience on this subject and a low level of knowledge, thus hindering consolidation of this knowledge.…”
Section: Discussionmentioning
confidence: 63%
“…11,14 The findings of the present study revealed that, in general, the level of knowledge of the dentists interviewed was low, notwithstanding the existence of clinical protocols in the literature that indicate the most adequate treatment approaches for each type of injury. 8,15 There is a low incidence of dentoalveolar traumas in clinical practice and, as a result, there is little experience on this subject and a low level of knowledge, thus hindering consolidation of this knowledge.…”
Section: Discussionmentioning
confidence: 63%
“…The dentist should be able to indicate effective therapeutic measures that provide the best possible prognosis. However, factors such as the severity of trauma, stage of root formation, time elapsed since the trauma, and adverse issues regarding the application of the techniques, will influence the treatment success (4).…”
Section: Discussionmentioning
confidence: 99%
“…The dentist can have difficulty making a correct diagnosis and establishing an effective treatment plan for injuries that do not occur daily (4). In many situations, the total extraction of a tooth is not acceptable to the family and the preservation of the tooth structure gives an emotionally and socially positive response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical knowledge and clinical experience are essential to establish an accurate diagnosis and provide appropriate treatment plan [5]. Most of these types of fracture require a multidisciplinary approach and the treatment of choice will depend on a number of factors such as: length of fracture [2,3,[6][7][8], biological width invasion [2,5,9,10], presence of pulp exposure, stage of root development [2,[5][6][7][8]11,12], soft tissue injuries [3,7,12,13], presence of concomitant periodontal trauma [3,7,8], presence / absence of fractured fragment and its adaptation, occlusion, esthetics, time, and available resources [2,[8][9][10][11][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%